Evaluating training programs : the four levels - Kirkpatrick, Donald L. (Berrett-Koehler, 2006)
The "Kirkpatrick Model" for evaluating training programs is the most widely used approach in the corporate, government, and academic worlds. First developed in 1959, it focuses on four key areas: reaction, learning, behavior, and results. This book provides a comprehensive guide to Kirkpatrick's four-level model, along with detailed case studies that show how the approach is used successfully in a wide range of programs and institutions. The third edition revises and updates existing material and includes new strategies for managing change effectively